2021
DOI: 10.4208/cicp.oa-2020-0097
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Faddeev-Merkuriev Equations in Total Orbital Momentum Representation via Spline Collocation and Tensor Product Preconditioning

Abstract: The computational approach for solving the Faddeev-Merkuriev equations in total orbital momentum representation is presented. These equations describe a system of three quantum charged particles and are widely used in bound state and scattering calculations. The approach is based on the spline collocation method and exploits intensively the tensor product form of discretized operators and preconditioner, which leads to a drastic economy in both computer resources and time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…We have proposed and implemented an approach for solving the quantum three-body problem which combines both a theoretically sound technique and a computationally efficient algorithm [10]. It is based on solving the Faddeev-Merkuriev (FM) equations [11] in total orbital momentum representation [12].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…We have proposed and implemented an approach for solving the quantum three-body problem which combines both a theoretically sound technique and a computationally efficient algorithm [10]. It is based on solving the Faddeev-Merkuriev (FM) equations [11] in total orbital momentum representation [12].…”
mentioning
confidence: 99%
“…It is based on solving the Faddeev-Merkuriev (FM) equations [11] in total orbital momentum representation [12]. Our earlier calculations [10] have shown that our approach makes for highly precise calculations of the bound state energies for the states with high total orbital momentum. Here we apply it to scattering problems and perform a series of calculations of antihydrogen formation cross sections for the reaction (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations